Computational BIM tool for automated LEED certification process - Dubljević, Sanja; Tepavčević, Bojan; Markoski, Branko; Anđelković, Aleksandar S. (Energy and buildings, 2023)
•New computational BIM workflow automates the achievement of certain LEED credits.•Presented tool enables real-time visibility of LEED credits achievement.•Certain LEED credits are parametrized using VPL in BIM environment.•The proposed tool can be applied to other GBCS and also to assess existing buildings. Building information modeling (BIM) and sustainable building certification integration have been the focus of several studies in recent years, aiming to create a simpler and more effective building certification process. This paper describes a novel computational tool for architects and engineers, considering that the certification process takes place in a work environment that is familiar to them. The goal is to present a method for developing a computational tool that will automate the process of verifying the achievement of certain Leadership in Energy and Environmental Design (LEED) credits using visual programming in a BIM environment. In this way, designers can have an insight into the achievement of certain LEED credits at any phase during the design process. Considering the complexity of the digital parameterization of LEED credits, this method includes the achievement of three credits listed in the Material and Resources chapter of the LEED for Building Design and Construction protocol. Apart from similar research, the presented tool enables visibility of real-time LEED credits achievement at every moment of the design, from the building concept development to the final stage. The presented method creates space for the elaboration on the other LEED credits, as well as research in the area of applicability to other green rating certification programs and evaluation of existing building stock.